Integration of transcriptomics and metabolomics reveals the responses of the maternal circulation and maternal-fetal interface to LPS-induced preterm birth in mice - Cao, Xianling; Zhou, Xuanyou; Chen, Songchang; Xu, Chenming (Frontiers in Immunology, 2023)
Background Term birth (TB) and preterm birth (PTB) are characterized by uterine contractions, rupture of the chorioamniotic membrane, decidual activation, and other physiological and pathological changes. In this study, we hypothesize that inflammation can cause changes in mRNA expression and metabolic stability in the placenta, decidua, chorioamniotic membrane, uterus and peripheral blood, ultimately leading to PTB. Methods To comprehensively assess the effects of inflammation on mRNA expression and metabolite production in different tissues of pregnancy, we used a mouse PTB model by intraperitoneally injecting lipopolysaccharide (LPS) and integrated transcriptomics and metabolomics studies. Results Our analysis identified 152 common differentially expressed genes (DEGs) and 8 common differentially expressed metabolites (DEMs) in the placenta, decidua, chorioamniotic membrane, uterus, and peripheral blood, or placenta and uterus after LPS injection, respectively. Our bioinformatics analysis revealed significant enrichment of the NOD-like receptor signaling pathway (mmu04621), TNF signaling pathway (mmu04668), IL-17 signaling pathway (mmu04657), and NF-kappa B signaling pathway in the transcriptomics of different tissues, and Hormone synthesis, Lysosome, NOD-like receptor signaling pathway, and Protein digest and absorption pathway in metabolomics. Moreover, we found that several upstream regulators and master regulators, including STAT1, STAT3, and NFKB1, were altered after exposure to inflammation in the different tissues. Interaction network analysis of transcriptomics and metabolomics DEGs and DEMs also revealed functional changes in mice intraperitoneally injected with LPS. Conclusions Overall, our study identified significant and biologically relevant alterations in the placenta, decidua, chorioamniotic membrane, uterus, peripheral blood transcriptome and the placenta and uterus metabolome in mice exposed to LPS. Thus, a comprehensive analysis of different pregnancy tissues in mice intraperitoneally injected with LPS by combining transcriptomics and metabolomics may help to systematically understand the local and systemic changes associated with PTB caused by inflammation.